(untitled) (World Bulletin of Social Sciences, 2024)
The goal of this article is to give explicit information on definitions of corpus linguistics, electronic linguistic corpus, and corpus technologies. A brief historical background on the development of corpora and corpus linguistics was given. Morover, the types and advantages of corpora were discussed.